2016
DOI: 10.1021/jacs.6b06277
|View full text |Cite
|
Sign up to set email alerts
|

The Competing Mechanisms of Phosphate Monoester Dianion Hydrolysis

Abstract: Despite the numerous experimental and theoretical studies on phosphate monoester hydrolysis, significant questions remain concerning the mechanistic details of these biologically critical reactions. In the present work we construct a linear free energy relationship for phosphate monoester hydrolysis to explore the effect of modulating leaving group pKa on the competition between solvent- and substrate-assisted pathways for the hydrolysis of these compounds. Through detailed comparative electronic-structure stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
80
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 53 publications
13
80
1
1
Order By: Relevance
“…We previously suggested that in the absence of metal ions, the preferred pathway for the hydrolysis of phosphate monoesters with good leaving groups is one involving a loose, dissociative transition state [19,20]. We demonstrate that for both compounds studied here, the presence of magnesium ions increases the energetic difference between substrate-and solvent-assisted pathways, creating a greater preference for a solventassisted pathway than in the absence of the metal.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…We previously suggested that in the absence of metal ions, the preferred pathway for the hydrolysis of phosphate monoesters with good leaving groups is one involving a loose, dissociative transition state [19,20]. We demonstrate that for both compounds studied here, the presence of magnesium ions increases the energetic difference between substrate-and solvent-assisted pathways, creating a greater preference for a solventassisted pathway than in the absence of the metal.…”
Section: Introductionmentioning
confidence: 55%
“…[7,8] and references cited therein). To partially address this issue, we recently performed detailed comparisons of a range of phosphate monoester dianions with different leaving groups, examining both leaving group effects and the effect of including explicit microsolvation in the calculations [19,20]. In addition to reasonable quantitative agreement between experimental and calculated activation free energies, our calculations reproduced both the linear free energy relationship for phosphate monoester dianion hydrolysis, as well as the experimentally observed kinetic isotope effects for p-nitrophenyl phosphate hydrolysis [19].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, DFT methods have been employed in many computational studies of phosphoryl transfer reactions in gas phase, with implicit solvent models or in the active site of enzymatic systems. 87,89,[160][161][162][163] Among the methods that follows this theory, the functional Becke three-parameter Lee-Yang-Parr (B3LYP) 94,95 has been the one selected to use in this PhD Thesis. This functional has been employed in a variety of systems, [164][165][166][167] including works of phosphate hydrolysis 81,107,168 and in phosphoryl transfer reactions in kinases 48,89,169 giving activation energies in agreement with results of experimental measurements.…”
Section: -Methods Based In Density Functional Theorymentioning
confidence: 99%